Performance of the UV Multinode Network Under the Lossless Contention MAC Protocol - Cheng Li (IEEE Photonics Journal, 2022)
Ultraviolet (UV) networks are important approaches to modern wireless communications owing to their unique characteristics, such as non-line-of-sight communication, strong anti-interference ability, and all-weather working mode. Given the lack of media access control (MAC) protocols suitable for UV networks at present, a novel UV lossless contention MAC (UVLLC-MAC) protocol is proposed herein based on UV physical properties. A fully connected finite-population multinode UV model is adopted, and its network performance is systematically derived and mathematically analyzed under the UVLLC-MAC protocol. Compared with the time-slot ALOHA protocol, the UVLLC-MAC protocol achieves 36.7% better throughputs, with 13.2% drop in packet loss rates, and the excellent performance of the protocol is obtained and fully verified. The UVLLC-MAC protocol can provide guidance for multinode and multiservice UV networking.